ON GEOMETRIC INTERPRETATION OF THE SIMPLEX METHOD: A REVIEW - VIJ, ASHU (International Journal of Mathematical Archive, 2018)
The simplex method is the computation procedure to obtain the minimum (optimum) feasible solution of an optimization problem. This method starts with an initial basic feasible solution and a sequence of basic feasible solutions is obtained such that value of objective function at each member is less than the proceeding value. In this paper the geometric interpretation of the algebraic computations of the simplex procedure is reviewed. The basic concepts and other geometric properties used for this interpretation are also discussed.